Women's writing and Muslim societies : the search for dialogue, 1920-present - Gemie, Sharif (University of Wales Press, 2012)
An analysis of a hundred prominent, commercially successful works by women, both Muslim and non-Muslim, concerning Muslim living in the Middle East, North Africa, Europe, the UK and the USA.